DIDACTIC PRINCIPLES OF PHYSICAL EDUCATION CHILD LIFE - Alixonova Dilbar Muxtarovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article contains a number of opinions about the role of physical culture in the life of the nation and in the development of the state, and special attention is paid to its teaching as a subject in family and secondary special education centers. In addition, the article also discusses the historical stages of the emergence of physical culture and education as a science, and also mentions a number of factors in the emergence of this science hoping to add contribution to the life of humans’ healthy life.